INTERNET ADVERTISEMENT ANALYSIS: TASK-BASED LANGUAGE LEARNING TO PROMOTE HIGHER ORDER THINKING IN EFL TEACHING - Muh. Basuni (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Internet provides plentiful sources for language learning. However, advertisement in internet so far is just treated as commodity promotion. Therefore, students will look at the advertisement only if they are searching products to purchase. Anyway, advertisement in internet can be utilized to improve students’ critical and creative thinking through the introduction of higher order thinking at English class. This article proposes a teaching procedure to improve students’ critical and creative thinking by integrating the task-based language learning and the higher order thinking skills, using the product advertisement in internet as the resources.